1993
DOI: 10.1152/ajpcell.1993.264.4.c783
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous ATP induces a limited cell cycle progression of arterial smooth muscle cells

Abstract: Because exogenous ATP is suspected to influence the proliferative process, its effects on the cell cycle progression of arterial smooth muscle cells were studied by investigating changes in the mRNA steady-state level of cell cycle-dependent genes. Stimulation of cultured quiescent smooth muscle cells by exogenous ATP induced chronological activation not only of immediate-early but also of delayed-early cell cycle-dependent genes, which were usually expressed after a mitogenic stimulation. In contrast, ATP did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 27 publications
4
44
0
1
Order By: Relevance
“…Moreover, extracellular ATP may be of importance in the growth regulation of mammalian cells. Stimulation of DNA synthesis has been reported for a variety of cultured cells including mouse fibroblasts, A431 epidermoid carcinoma cells and DDT,-MF-2 vas deferens cells (Huang et al, 1989), in aortic smooth muscle cells (Malam-Souley et al, 1993;Erlinge et al, 1993), endothelial cells (Van Daele et al, 1992) and mesangial cells (Schulze-Lohoff et al, 1992). It has been reported that activation of PKC and phospholipase A2 and subsequent production of prostaglandin E2 and cyclic AMP formation are obligatory early steps in a pathway resulting in ATPdependent mitogenesis Huang et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extracellular ATP may be of importance in the growth regulation of mammalian cells. Stimulation of DNA synthesis has been reported for a variety of cultured cells including mouse fibroblasts, A431 epidermoid carcinoma cells and DDT,-MF-2 vas deferens cells (Huang et al, 1989), in aortic smooth muscle cells (Malam-Souley et al, 1993;Erlinge et al, 1993), endothelial cells (Van Daele et al, 1992) and mesangial cells (Schulze-Lohoff et al, 1992). It has been reported that activation of PKC and phospholipase A2 and subsequent production of prostaglandin E2 and cyclic AMP formation are obligatory early steps in a pathway resulting in ATPdependent mitogenesis Huang et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Transfection-Rat aortic SMCs were prepared from the thoracic aortas of Wistar rats and cultured as described previously (26). SMCs from passages 10 to 20 were used.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies of VSMC have shown that extracellular nucleotides induce cell cycle progression and proliferation [6][7][8]. For example, UTP has chemotactic effects on VSMC migration which involve Rho and mitogen-activated purine signaling via P2Y receptor subtypes [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%